Rumah Tanpa Uang Muka bagi Masyarakat Berpenghasilan Rendah Menurut Hukum Administrasi Negara - Bayu Gusmaizal Chanra (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2019)
The need for housing (house) is a very important basic need besides the clothing and food needs. Especially if the house is livable and is purchased at an affordable price. The Regional Government is obliged to provide easy housing for low income community. The form of convenience provided is in the form of house without a down payment or better known as DP 0 Rupiah house. The DP 0 rupiah house program is a program of the Provincial Government of DKI Jakarta that aims to make it easier for residents who do not yet have a house to own their own property but are hampered by a substantial DP problem. Based on the foregoing, related to the financing policy adopted by the Provincial Government of DKI Jakarta in the form of a DP 0 rupiah house program needs to be analyzed comprehensively according to state administrative law.Keywords: low income community, DP 0 rupiah house, state administrative law.